Analysis Defect Products in Silencers Using the New Seven Tools Method - Annandita, Alifia Rizky; Rochmoeljati, Rr. (Newinera Publisher, 2025)
Quality is important for a product so that it can have more value than other products. To maintain quality, quality assurance (quality) is required. As is the case with silencer products produced by CV. Nyoto Plastik, silencer is a product that must maintain its quality value. Therefore, many defects in silencer products must be repaired by analyzing the causes of the defects. Based on research, the average defect in this silencer product reaches 10% within one year. New Seven Tools is a method for finding out the causes of defects based on humans, methods, materials, machines or the environment by using the seven tools contained in it. Therefore, this research aims to help maintain the quality of silencers by analyzing the causes of defects and providing suggestions for improvements to minimize defects that occur using the New Seven Tools method.